Bobby Deen's everyday eats - Deen, Bobby (New York : Ballantine Books Trade Paperbacks, 2014)
"Bobby Deen is back with 120 simple, mouthwatering recipes--all under 350 calories--that can be prepared from start to finish in under 30 minutes. Now, in Bobby Deen's Everyday Eats, Bobby helps you get a tasty and good-for-you dinner on the table in no time flat, with dozens of delectable recipes all under 350 calories and all prepared in less than 30 minutes. He even includes nutritional information for each and every recipe."--
Introduction -- Salad meals -- Soup suppers -- Seafood -- Poultry -- Meat -- Meatless mains -- Fire up the grill -- SEasonal sides -- Good for you grains -- Sweet dreams.
"All under 350 calories, all under 30 minutes"--Cover.
Includes index.
Keywords: Quick and easy cooking; Low-calorie diet -- Recipes; Cooking, American; Cookbooks